METODE SIMPLE ADDITIVE WEIGHTING UNTUK SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA GURU - Astuti, Reny Wahyuning (JURNAL AKADEMIKA, 2016)
The development of science and technology offers facilities in carrying out the activity and employment. The presence of this technology is intended to achieve better results in achieving the accuracy of information. With a good information system will provide easy access to a variety of things to be desired. Implementation of technology is the application of soft computing that can help improve a persons performance at work and overcome existing within the school environment as well as decision support systems. One method that is used by principals to improve education quality by assessing the performance of teachers. Its aim is to determine the level of quality teachers in schools with an application based decision support system, it is intended that the assessment would be far more effective. This is done with the input of several criteria as indicators and generate performance assessment reports.